Playing Techniques on Saw Duang and Haegeum Fiddles: Similarities and Differences - Vejakorn, Onuma; Seemuang, Jatuporn; Pornprasit, Kumkom (Journal of Fine and Applied Arts Khon Kaen University, 2023)
The research of Playing Techniques on Saw Duang and Haegeum Fiddles: similarities and differences has three purposes, firstly, to study the physical characteristics and the practice of Saw Duang and Haegeum, secondly, to study strategies in playing Saw Duang and Haegeum and lastly, to study the similarities and differences of Saw Duang and Haegeum. The researcher has studied data from the fieldwork and analyzed them by using a qualitative research methodology. The study results show that there are 10 Physical and Practical Characteristics of Saw Duang and Haegeum, three practices. Saw Duang and Haegeum playing Techniques can be divided into ensemble and solo. Similarities and differences between their physical characteristics are different of Rad-ok and bow tension. Saw Duang must be pressed the string with the fingertips and controlled the bow fit while Haegeum must be pressed the strings with a second finger joint. The ring finger and little finger have two sound positions. Haegeum uses more weight to control has more dynamics. The left-hand techniques share four techniques which are: 1.Prom pid is like Three of nonghyeon. 2.Changing finger position on Haegeum’s Ulim and Nelim. 3.“Tod New” 4.“Kratop Siang” matches the two-sound pressing with the middle finger. The differences of Saw Duang are found in 4 techniques: Prom perd, finger rolling, dapping, and rubbing. Haegum has two techniques: Twesong and ornamental ( ). The right-hand techniques share 10 likeness There are two specific Saw Duang techniques: Yoy Jangwa and Sa Euk bow. Haegeum’s characteristics include six techniques which are about controlling the mood of the song.